Pengembangan Waktu Bersantai Dan Rekreasi Untuk Wisata Lanjut Usia Di Kawasan Wisata Montigo Resort, Batam - Hariyanto, Oda I. B.; Anastasia, Sherly (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
This study aims to develop a recreation and recreation model of future life in Montigo Resorts Batam to discover future tourists at this facility. The basis of this study is that Montigo Resorts has an afterlife in tourism. Currently, Montigo Resorts is growing rapidly, but Montigo Resorts is still a choice for this age group. 20 foreign tourists selected as respondents for this study. Their trips are planned independently and they come as a couple to relax. Data collection was done through interviews, observations and document research. Adventure and play are activities that young people do choose. Welcoming late-night tourists usually focuses on themes of late-night activities, entertainment, and entertainment during the hotel stay. Following this study, a happy and healthy passive comfort model was proposed. Standardization of comfort facilities for the elderly is a recommended program for public tourism facilities as well as resorts, restaurants and cafes and is a recommended strategy for Batam to maintain its presence as a tourist destination for tourists from around the world. Keywords: Montigo Resorts, leisure and recreation, Activities, Later life tourist, tourist facilities